EFL COLLEGE TEACHERS’ AWARENESS ON CAR: A case study at Universitas Muhammadiyah Jember - Tanzil Huda; Indah Rakhmawati Afrida; Mariyae Chelong (Journey: Journal of English Language and Pedagogy, 2020)
Nobody can claim that all instructions are free from problems. Realizing that all instruction are potential to have problems, college teachers should do reflective practices. One of the do reflective practices which can be done integratively and sytematically with their instructions is classroom action research (CAR). The present study tried to investigate the lecturers’ perception on CAR. The study focused on the indentifi-cation of the lecturers’ awareness on CAR and digging up the the factors affected the lecturers perception on CAR. The study employed survey method which posited qualitative approach. The study revealed that the leacturers’ awareness on CAR was relatively low. It also indicated that there were some factors which affected the lecturers’ awareness on CAR i.e., 1) the lecturer’s prior education or pre-service education; 2) their involvement in scientific forums; 3) self-regulated learning by reading books on CAR.